AB1094 SCAR IMAGING ECHOCARDIOGRAPHY WITH ULTRASOUND MULTI-PULSE SCHEME [eSCAR] FOR THE DETECTION OF MYOCARDIAL FIBROSIS IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS: PRELIMINARY RESULTS. (2nd June 2020) - Giollo, A.; Vinco, G.; Orsolini, G.; Cioffi, G.; Adami, G.; Fassio, A.; Idolazzi, L.; Gatti, D.; Ribichini, F. L.; Rossini, M.; Viapiana, O.
Abstract : Background: Myocardial fibrosis is a severe complication of immune-mediated diseases, occurring in up to 30% of systemic lupus erythematosus (SLE) patients. Cardiovascular magnetic resonance imaging allows myocardial scar detection in SLE patients, but it is costly, time consuming, and unfit for patients with renal disease. Scar imaging echocardiography with ultrasound multi-pulse scheme (eSCAR) is a novel and promising technique that proved to be effective in detecting ischemic myocardial scars in patients with coronary artery disease (CAD). Objectives: To evaluate if the eSCAR technique is feasible and to better characterize SLE patients with cardiac involvement by eSCAR. Methods: We recruited consecutive patients with SLE classified according to the 2019 EULAR/ACR recommendations. Patients with diabetes mellitus, obesity, prior cardiovascular (CV) disease or anti-phospholipid (aPL) syndrome were excluded. Eligible participants underwent a thorough clinical assessment and a full echocardiography examination, including the eSCAR technique. Data on clinical variables were collected; disease activity was estimated by the SLE Disease Activity Index (SLEDAI) score. Lupus flare was defined as new/worse clinical signs and symptoms and/or lab measurements and a change/increase in treatment. Patients were compared according to the presence or absence of eSCAR. In this preliminary report, only descriptive analyses are provided. Continuous data are reported as median [25 th ; 75 th percentile]. Results: We enrolled fifteen patients diagnosed with SLE (age 45 years [36; 47], disease duration 14 years [12; 20]), 13 (87%) were females. Median SLEDAI was 5 [2; 8]. The most frequent disease involvement included arthritis (73%), skin and mucous membranes (60%), lupus nephritis (47%) and cytopenias (47%). Patients had received treatment for lupus with 5 drugs [5; 8]. Cumulative prednisone dosage was 25 g [20; 44], whilst the current daily dosage of prednisone was 4 mg [0.0; 5.0]. Hypertension was present in 4 (27%) and hypercholesterolemia in 2 (13%) subjects; 4 patients (27%) were current or past smokers. The eSCAR technique was feasible in all participants with no adverse effects. Myocardial scars were detected in 2 patients (eSCAR-positive 13%; figure and table); eSCAR positive patients were females and had no history of cardiovascular involvement (including pericarditis); they had at least one relapse within the prior 12 months before enrollment; at least one cardiovascular risk factor was found in both patients (one was a smoker and the other one had hypertension); none received prior treatment with cyclophosphamide or rituximab; they had no renal involvement; arthritis and cytopenia were the prominent features of disease; anti-dsDNA titer was higher than eSCAR-negative patients. Conclusion: Echocardiography allowed detection of myocardial scars in patients with SLE. Our preliminary data show that eSCAR is feasible and well tolerated in a SLE population. Further data from this ongoing study will help investigate whether eSCAR might improve risk stratification, by identifying myocardial involvement in SLE patients with a more active disease. Acknowledgments: This study was granted by Gruppo LES Italia Onlus Disclosure of Interests: Alessandro Giollo: None declared, Giulia Vinco: None declared, Giovanni Orsolini: None declared, Giovanni Cioffi: None declared, Giovanni Adami: None declared, Angelo Fassio Speakers bureau: Angelo Fassio reports personal fees from: Abiogen and Novartis, outside the submitted work., Luca Idolazzi: None declared, Davide Gatti Speakers bureau: Davide Gatti reports personal fees from Abiogen, Amgen, Janssen-Cilag, Mundipharma, outside the submitted work., Flavio Luciano Ribichini: None declared, Maurizio Rossini Speakers bureau: AbbVie, Abiogen, Amgen, BMS, Eli-Lilly, Novartis, Pfizer, Sanofi, Sandoz and UCB, Ombretta Viapiana: None declared